Utilizing video conferencing with families of critically ill non-COVID-19 patients during the pandemic curfew - Abdulrahman H Balkhoyor; Mohmmed A Algamdi; Mahmoud S Alyamany; Norah S Bin Saad; Hani Lababidi; Mohammed A Hussein; Ayman M Kharaba; Mohammed A Almaani (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background COVID-19 pandemic curfew made it difficult for families to communicate with their loved ones while hospitalized in the intensive care unit (ICU). A hybrid telephone and video conferencing model (VC) was created as a method of communication. This study aims to assess the satisfaction of critically ill non-COVID-19 patients and their families with VC as a mean of communication during the curfew. # Methods A prospective observational study was conducted in two academic hospitals. Family visits were replaced by VC during the curfew and visitation restriction. To assess the satisfaction with VC, families were surveyed twice while patients were surveyed once during the ICU admission. # Results Among 81 family representatives initially surveyed, 26 (32.1%) underwent a follow-up survey. On a scale of 1-10, high general satisfaction was reported by family representatives in the initial and follow-up surveys (8.68 ± 1.66 and 8.31 ± 1.89, respectively). General satisfaction of 9.64 ± 0.67 was reported by the patients who were surveyed during their ICU admission (n=11). Higher patient's Glasgow Coma Scale at the time of VC and increased number of VC sessions were associated with higher family satisfaction (*P*=0.001 and *P*=0.019, respectively). Among family representatives, more than 70% preferred video conferencing over traditional means of communication during the curfew. # Conclusions Family representatives and their critically ill non-COVID-19 patients were highly satisfied with video conferencing as a mean of communication during the curfew and visiting restriction. Video conferencing offers a great way of communication during pandemics, such as COVID-19.